Effects of Preoperative HbA1c Levels on the Postoperative Outcomes of Coronary Artery Disease Surgical Treatment in Patients with Diabetes Mellitus and Nondiabetic Patients: A Systematic Review and Meta-Analysis - Jinjing Wang; Xufei Luo; Xinye Jin; Meng Lv; Xueqiong Li; Jingtao Dou; Jing Zeng; Ping An; Yaolong Chen; Kang Chen; Yiming Mu (Journal of Diabetes Research)
Aims. To investigate the effect of preoperative HbA1c levels on the postoperative outcomes of coronary artery disease surgery in diabetic and nondiabetic patients. Methods and Results. The MEDLINE (via PubMed), Cochrane Library, Web of Science, Embase, Wanfang Data, China National Knowledge Infrastructure (CNKI), and Chinese Biology Medicine (CBM) databases were used to search the effects of different preoperative HbA1c levels on the postoperative outcomes of coronary artery disease surgical treatment in diabetic and nondiabetic patients from inception to December 2018. Two review authors worked in an independent and duplicate manner to select eligible studies, extract data, and assess the risk of bias of the included studies. We used a meta-analysis to synthesize data and analyze subgroups, sensitivity, and publication bias as well as the GRADE methodology if appropriate. The literature search retrieved 886 records initially, and 23 cohort studies were included in the meta-analysis. In this meta-analysis, we found that there was a reduced incidence of surgical site infections (OR=2.94, 95% CI 2.18-3.98), renal failure events (OR=1.63, 95% CI 1.13-2.33), and myocardial infarction events (OR=1.69, 95% CI 1.16-2.47), as well as a shortened hospital stay (MD=1.08, 95% CI 0.46-1.71), in diabetic patients after coronary artery disease surgical treatment with lower preoperative HbA1c levels. For nondiabetic patients, a higher preoperative HbA1c level resulted in an increase in the incidence of mortality (OR=2.23, 95% CI 1.01-4.90) and renal failure (OR=2.33, 95% CI 1.32-4.12). No significant difference was found between higher and lower preoperative HbA1c levels in the incidence of mortality (OR=1.06, 95% CI 0.88-1.26), stroke (OR=1.49, 95% CI 0.94-2.37), or atrial fibrillation (OR=0.94, 95% CI 0.67-1.33); the length of ICU stay (MD=0.20, 95% CI -0.14-0.55); or sepsis incidence (OR=2.49, 95% CI 0.99-6.25) for diabetic patients or for myocardial infarction events (OR=1.32, 95% CI 0.27-6.31) or atrial fibrillation events (OR=0.99, 95% CI 0.74-1.33) for nondiabetic patients. The certainty of evidence was judged to be moderate or low. Conclusion. This meta-analysis showed that higher preoperative HbA1c levels may potentially increase the risk of surgical site infections, renal failure, and myocardial infarction and reduce the length of hospital stay in diabetic subjects after coronary artery disease surgical treatment and increase the risk of mortality and renal failure in nondiabetic patients. However, there was great inconsistency in defining higher preoperative HbA1c levels in the studies included; we still need high-quality RCTs with a sufficiently large sample size to further investigate this issue in the future. This trial is registered with CRD42019121531.